Selection and validation of genes related to oxidative stress production and clearance in macrophages infected with Mycobacterium tuberculosis - Su, Renchun; Yuan, Jinfeng; Gao, Tianhui; Liu, Yuhong; Shu, Wei; Wang, Yufeng; Pang, Yu; Li, Qi (Frontiers in Cellular and Infection Microbiology, 2023)
Background In the fight against tuberculosis, besides chemotherapy, the regulation of oxidative stress (OS) has also aroused people’s interest in host-oriented therapy. However, there is limited research on the genes involved in reactive oxygen species (ROS) production and clearance in macrophages infected with Mycobacterium tuberculosis (MTB). This study analyzes and explores this to provide a basis for exploring new targets for antituberculosis treatments. Methods We established a macrophage model infected with MTB, counted intracellular bacteria, and determined the ROS produced using flow cytometry. We conducted ribonucleic acid sequencing, screened differentially expressed genes through transcriptomic methods, and validated the expression of them through reverse transcription-quantitative polymerase chain reaction. Results The ROS of macrophages increased with intracellular bacteria at 4 h after infection with MTB and reached its peak at 48 h, surpassing the uninfected macrophages (p < 0.05). A total of 1,613 differentially expressed genes were identified after infection with MTB, of which 458 were associated with ROS, with over 50% involved in the response of organelles and biological processes to stimuli. We analyzed and identified six genes. After macrophage infection with MTB, the expression of CAMK2B increased, whereas the expression of CYBB decreased (p < 0.05). The expression of GPX3 and SOD2 increased, whereas the expression of CAT decreased (p < 0.05). Conclusion The ROS-related differentially expressed genes between MTB infected and uninfected macrophages may be related to some organelles and involved in various biological processes, molecular functions, and signaling pathways. Among them, CAMK2B, GPX3, and SOD2 may be related to ROS.